Database design for mere mortals : a hands-on guide to relational database design - Hernandez, Michael J. (Michael James), 1955- (Addison-Wesley Developers Press, 1997)
Database design expert Michael J. Hernandez introduces the core concepts of design theory and method without the technical jargon. With its hands-on approach and a wealth of practical examples, Database Design for Mere Mortals will provide any developer with a common-sense design methodology for developing databases that work.